Peningkatan Konsentrasi Belajar Matematika Menggunakan Model Pembelajaran Picture And Picture Di SDN Wanasari 01 - Chrisnaji Banindra Yudha; Dyah Anungrat Herzamzam; Nurmulia Diniarti; Meti Lasminingsih (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This research is determine the increase in students' concentration in study mathematics at SDN Wanasari 01. The subjects in this study were 36 elementary school students. This research method is classroom action research which consists of four components, namely planning, implementing, observing, and reflecting. Data collection techniques in this study used observation, interviews, and documentation. Based on the results of the study, that in cycle 1 the process of learning mathematics was said to be not good enough, because most students still lacked concentration on learning. In addition, the teacher's use of the picture and picture model has not been fully implemented at every meeting. Meanwhile, in cycle 2, students' concentration in mathematics has increased.